Transcontinental patterns in floral pigment abundance among animal-pollinated species - Narbona, Eduardo; Del Valle, Jose C.; Whittall, Justen B.; León-Osper, Melissa; Buide, M. Luisa; Pulgar, Iñigo; Camargo, Maria Gabriela Gutierrez [UNESP]; Morellato, Leonor Patricia Cerdeira [UNESP]; Rodríguez-Castañeda, Nancy; Rossi, Victor; Conrad, Katie; Hernandez Mena, Josephine; et al. (Springer Nature, 2025)
Flower color arises primarily from pigments that serve dual functions: attracting pollinators and mitigating environmental stresses. Among major pigment types, anthocyanins and UV-absorbing phenylpropanoids (UAPs) fulfill one or both roles and should be widespread. Our review of the UV-vis absorption profiles of major floral pigments demonstrates that UAPs are the primary UV protectants. Next, we analyzed the floral pigment composition of 926 animal-pollinated species from California, Southern Spain, and Southeastern Brazil. UAPs were ubiquitous (the “dark matter” of the flower). Among the remaining pigment types, ~ 56% of species had anthocyanins, ~ 37% had carotenoids, and ~ 17% had chlorophylls (some species had > 1 pigment type). Pigment abundance varied in response to abiotic and biotic factors, particularly with pollinator type in California. Despite regional differences in environmental filtering, pollination guilds, and relatedness, UAPs are omnipresent and there is a transcontinental stable distribution of flower colors and their underlying floral pigments.